The Distributional Consequences of Public School Choice - Avery, Christopher; Pathak, Parag A. (American Economic Review, 2021)
The Distributional Consequences of Public School Choice by Christopher Avery and Parag A. Pathak. Published in volume 111, issue 1, pages 129-52 of American Economic Review, January 2021, Abstract: School choice systems aspire to delink residential location and school assignments by allowing childre...